Colonization of a Central Venous Catheter by the Hyaline Fungus Fusarium solani Species Complex: A Case Report and SEM Imaging - Alberto Colombo; Giuseppe Maccari; Terenzio Congiu; Petra Basso; Andreina Baj; Antonio Toniolo (Case Reports in Medicine)
The incidence of opportunistic infections by filamentous fungi is increasing partly due to the widespread use of central venous catheters (CVC), indwelling medical devices, and antineoplastic/immunosuppressive drugs. The case of a 13-year-old boy under treatment for acute lymphoblastic leukemia is presented. The boy was readmitted to the Pediatric Ward for intermittent fever of unknown origin. Results of blood cultures drawn from peripheral venous sites or through the CVC were compared. CVC-derived bottles (but not those from peripheral veins) yielded hyaline fungi that, based on morphology, were identified as belonging to the Fusarium solani species complex. Gene amplification and direct sequencing of the fungal ITS1 rRNA region and the EF-1alpha gene confirmed the isolate as belonging to the Fusarium solani species complex. Portions of the CVC were analyzed by scanning electron microscopy. Fungi mycelia with long protruding hyphae were seen into the lumen. The firm adhesion of the fungal formation to the inner surface of the catheter was evident. In the absence of systemic infection, catheter removal and prophylactic voriconazole therapy were followed by disappearance of febrile events and recovery. Thus, indwelling catheters are prone to contamination by environmental fungi.